Algebraic dynamics solution to and algebraic dynamics algorithm for nonlinear advection equation - Zhang, Hua; Lu, WeiTao; Wang, ShunJin (Science China. Physics, mechanics & astronomy, 2008)
Algebraic dynamics approach and algebraic dynamics algorithm for the solution of nonlinear partial differential equations are applied to the nonlinear advection equation. The results show that the approach is effective for the exact analytical solution and the algorithm has higher precision than other existing algorithms in numerical computation for the nonlinear advection equation.